Neural Response During a Mechanically Assisted Spinal Manipulation in an Animal Model: A Pilot Study - William R. Reed; Michael A.K. Liebschner; Randall S. Sozio; Joel G. Pickar; Maruti R. Gudavalli (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Introduction: Mechanoreceptor stimulation is theorized to contribute to the therapeutic efficacy of spinal manipulation. Use of mechanically-assisted spinal manipulation (MA-SM) devices is increasing among manual therapy clinicians worldwide. The purpose of this pilot study is to determine the feasibility of recording in vivo muscle spindle responses during a MA-SM in an intervertebral fixated animal model. Methods: Intervertebral fixation was created by inserting facet screws through the left L5-6 and L6-7 facet joints of a cat spine. Three L6muscle spindle afferents with receptive fields in back muscles were isolated. Recordings were made during MA-SM thrusts delivered to the L7 spinous process using an instrumented Activator IV clinical device.  Results: Nine MA-SM thrusts were delivered with peak forces ranging from 68-122N and with thrust durations of less than 5ms. High frequency muscle spindle discharge occurred during MA-SM. Following the MA-SM, muscle spindle responses included returning to pre-manipulation levels, slightly decreasing for a short window of time, and greatly decreasing for more than 40s. Conclusion: This study demonstrates that recording in vivo muscle spindle response using clinical MA-SM devices in an animal model is feasible.  Extremely short duration MA-SM thrusts (<5ms) can have an immediate and/or a prolonged (> 40s) effect on muscle spindle discharge. Greater peak forces during MA-SM thrusts may not necessarily yield greater muscle spindle responses. Determining peripheral response during and following spinal manipulation may be an important step in optimizing its' clinical efficacy. Future studies may investigate the effect of thrust dosage and magnitude. Pubmed link: https://www.ncbi.nlm.nih.gov/pubmed/26618202